Energy Efficiency in Buildings and Excess Summer Mortality in the UK - Abdi, Ali Mohamed; Arewa, Andrew; Tyrer, Mark; Ugulu, Rex Asibuodu (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
One of the main objective of the building design is to provide comfort and safety to occupants, particularly during adverse weather conditions. In most part of the world, people stay indoors during adverse weather conditions, thus increasing energy consumption. In UK, vulnerable people such as the elderly are highly affected with mortality rate during extreme weather conditions. The 2003 heatwave reached average of 38.5° C in the UK resulting in the death toll of 2,234. The 10 days period of extreme heat is thought to be the warmest about the last 500 years. Across Europe, the 2003 heatwave resulted in 20,000 deaths; in France alone, the number reached 15,000. Similarly, the 2018 summer heatwaves, reached 35.5°C contributing to 863 deaths. Yet, there is little research regarding impact of energy efficiency in building and deaths caused by excessive heatwaves in the UK. The study aims to investigate the impact of energy efficiency in buildings and excessive heatwave deaths among elderly people in the UK. Research question asked is; do energy efficiency programmes and policies contribute to excessive summer deaths in the UK? .The study adopted quantitative research method with participants drawn from low/average income households, in west midlands part of UK, between 2003/04 to 2017/18. Initial findings show that there is a significant relationship between energy efficiency adoption, government policies and excessive summer deaths.